Mobilização na aprendizagem da física escolar : uma análise a partir da relação com o saber - Maia, Lucas da Silva (2016)
The purpose of this dissertation is to identify the elements that favor (or not) students’ engagement in learning physics based on the relation to knowledge theoretical framework proposed by the French philosopher Bernard Charlot. In order to that, we characterized students relation to physics knowledge identifying their conceptions about school physics, school, the act of learning, themselves as learners at school and understand how their life and school experiences give light to the phenomena under study. We collected information from a population of 142 high school students from public or private schools at São Carlos. This PhD research was executed in three steps which the previous one oriented the actions implemented of the next one. During the first step, we applied a questionnaire in order to characterize students’ relation to school knowledge in general and students’ relation to physics knowledge and we analyzed the information collected using content analysis (analysis of categories). During the second step, we elaborated profiles of relation to physics knowledge implementing cluster analysis to a set of categories created in the previous step. During the third step, we interviewed 15 students in order to identify the elements the favors or not students’ engagement in Physics learning. We analyzed interviews contents using content analysis (analysis of themes). We concluded that the elements that favors or not students’ engagement in learning physics are related to physics knowledge itself, to teaching actions in physics classrooms and the effects those actions produce, to others and the relation the subject maintains to his/herself.